Potential of Pariangan Tanah Datar Hot Spring for domestic tourism/ Siska Mandalia and Rizal - Mandalia, Siska; Rizal (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The aim of this paper is to assess the potential of hot spring tourism for domestic tourism in Pariangan Tanah Datar Regency West Sumatera. The points that the authors see in this study are: hot springs potential for domestic tourists, tourist facilities and accessibility. The method used is descriptive and the participation of communities was included in the study's approach. Data collection is observation, structured interviews, and documentation. This study uses a qualitative descriptive method that is analyzed interpretatively using appropriate theories or literatures, then inductively draws conclusions to answer the existing problems. The results of the study explained about 1) The potential of hot springs, 2) Public facilities, and 3) The accessibility of tourism objects.